A Prospective Observational Study on Outcomes of Hepatitis B, Hepatitis C Patients in Gastroenterology Department of Tertiary Care Hospital - Thalla, Sreenu; Kamaraj, R.; Kavitha, A. (Journal of Neonatal Surgery, 2025)
Oral direct-acting antiviral (DAA) therapies have significantly improved the treatment outcomes for chronic hepatitis C virus (HCV) infection, achieving sustained virological response (SVR) rates exceeding 95%. However, co-infection with hepatitis B virus (HBV) and HCV presents greater clinical complexity than mono-infection with either virus. In this study, we evaluated the incidence of HBV reactivation during and three months post-DAA therapy, as well as the SVR rate at 12 weeks in patients with HBV/HCV co-infection. Among the study cohort, 361 patients (95.5%) achieved SVR. Factors associated with failure to achieve SVR included older age, lower platelet count, elevated blood creatinine levels, and increased liver stiffness measured by FibroScan. HBV reactivation occurred in 13 patients (4%), who had significantly higher baseline levels of ALT, serum creatinine, and HCV RNA viral load compared to those without reactivation. While DAA therapy is highly effective in achieving SVR in HBV/HCV co-infected patients, careful monitoring is essential due to the risk of HBV reactivation during and after treatment.